Анализ систем управления синхронными двигателями с постоянными магнитами при регулировании скорости вверх от номинальной - Толочко, Ольга Ивановна; Божко, Владислав Владимирович (НТУ "ХПИ", 2010)
In article possibilities and features of regulation of speed of synchronous engines with constant magnets in a range above the nominal are investigated. Working conditions and management strategy in the first, second and third zones of regulation are analyses. By means of mathematical modeling transients at two-zonal and three-zonal regulation are received. Directions of the further researches are planned.
Analysis of permanent magnet synchronous motor control systems in speed regulation up of nominal
Keywords: ротор; преобразователь частоты; статор; сопротивление; максимальный момент на ампер; максимальный момент на вольт; моделирование математическое